Association between Sleep Duration and Hypertension among Adults in Southwest China - Jie He; Quan He (Ubiquity Press, 2022)
Objective: This study aimed to evaluate the association between sleep duration and hypertension among adults in southwest China. Methods: Baseline variables were collected from a representative sample of 20,053 adults aged 23-98 years in southwest China who received physical examinations from January 2019 to December 2020. All participants were categorized into either a hypertension group or a non-hypertension group. Sleep duration was classified as short (<6 h/day), normal (6-8 h/day),or long (>8 h/day). Baseline variables were compared between individuals with and without hypertension by rank-sum tests for two independent samples or χ2 tests for nonparametric data. Multivariate logistic regression analysis was performed to evaluate the association between sleep duration and hypertension. Results: The overall incidence of hypertension was 51.2%. Unadjusted analysis showed that the risk of hypertension was higher in individuals with short (<6h/day) or long (>8h/day) sleep durations compared with those with a normal (6-8 h/day) sleep duration. The risk of hypertension was significantly increased by 30.1% in participants with a long (>8h/day) sleep duration compared with those with a normal (6-8h/day) sleep duration (OR = 1.301, 'P' < 0.010, 95%CI = 1.149-1.475). The risk of hypertension was also increased by 1.1% in participants with a short (<6h/day) sleep duration compared with participants with a normal (6-8h/day) sleep duration, but the difference was not significant (OR = 1.011,P= 0.849, 95%CI = 0.905-1.129). After fully adjusting for confounding factors (model 4), the risk of hypertension was increased significantly (by 25%) in individuals with a short (<6h/day) sleep duration (OR = 1.25, 'P' = 0.02, 95%CI = 1.036-1.508) but not in those with a long (>8h/day) sleep duration (17.5% increase) compared with participants with a normal (6-8h/day) sleep duration (OR = 1.175, 'P' = 0.144, 95%CI = 0.946-1.460). Conclusion: The results of this study indicate that a short (<6h/day) sleep duration is related to an increased risk of hypertension, suggesting that sleep helps to protect against hypertension.